Parametric analysis of carbon nanofiber effects on mechanical properties and abrasion resistance of GF/PPS hybrid composites (Fracture and Structural Integrity, 2026)
The focus of this research was to investigate the effects of carbon nanofiber (CNF) reinforcement on the mechanical performance, interfacial characteristics, and abrasive wear behavior of short glass fiber/polyphenylene sulfide (GF/PPS) hybrid nanocomposites intended for high-performance tribological applications. Melt processing was used to fabricate GF/PPS hybrid nanocomposites with 0, 0.4, and 0.8 wt% CNFs, which were then methodically characterized. Through π–π interactions between CNFs and the polymer matrix, FTIR measurements demonstrated enhanced interfacial compatibility while confirming the retention of the PPS chemical structure. The addition of CNFs demonstrated improved fiber–matrix adhesion and load transmission capability by increasing composite density, decreasing void content, and considerably improving interlaminar shear strength (23.7%) and hardness (20%). Studies on two-body abrasive wear showed significant decreases in wear loss and coefficient of friction (CoF), with the 0.8 wt% CNF-filled composite showing the best tribological performance because a stable and continuous lubricating tribo-film was formed. Applied load mostly controlled the CoF behavior, while sliding velocity and abrasive grit size primarily affected wear loss, according to statistical ANOVA data. With prediction errors under 6.5% and coefficient of determination (R²) values between 73% and 77%, regression models demonstrated strong predictive power. The change from severe micro-cutting, matrix deterioration, and fiber pull-out in unfilled composites to mild ploughing and protective tribo-layer development in CNF-reinforced composites was further validated by worn surface morphology. The CNF modified GF/PPS hybrid nanocomposites are promising materials for automotive transmission components, bearing cages, thrust washers, gears, and power plant chute liners operating under extreme abrasive wear conditions, as evidenced by the synergistic improvement in mechanical strength, interfacial bonding, and tribological stability.
Keywords: Glass fiber reinforced PPS composites; Carbon nanofibers; Mechanical properties; Taguchi method; Abrasive wear; Worn surface morphology